PREFERENCES OF ISLAMIC EDUCATIONAL INSTITUTIONS IN CHOOSING PAYROLL AT SHARIA BANKS - Hardiyani, Gianisha; Kurnia, Tuti; Hasbi, Sahlan (Universitas Airlangga, 2018)
This study aims to determine the most dominant factors that affecting the preferences of Islamic educational institutions in choosing payroll in Islamic banks. The research method used a quantitative approach with factor analysis technique. Data collection techniques used questionnaires and interview techniques from 30 Islamic educational institutions in Sukabumi. The results of this study indicate that service, facilities, image, religion, and reference groups are the most dominant factor or the main factor for the preference of Islamic educational institutions in choosing payroll in Islamic banks. While role factor and status, product, promotion, location and knowledge are the supporting factor for preference of Islamic education institution in choosing payroll in syariah bank.Keywords: Bank Syariah, Preferences, Payroll, Islamic educational institutions.